Determination of low concentrations of iron, arsenic, selenium, cadmium, and other trace elements in natural samples using an octopole collision/reaction cell equipped quadrupole‐inductively coupled plasma mass spectrometer. (17th March 2015) - Dial, Angela R.; Misra, Sambuddha; Landing, William M.
Abstract : Rationale: Accurate determination of trace metals has many applications in environmental and life sciences, such as constraining the cycling of essential micronutrients in biological production and employing trace metals as tracers for anthropogenic pollution. Analysis of elements such as Fe, As, Se, and Cd is challenged by the formation of polyatomic mass spectrometric interferences, which are overcome in this study. Methods: We utilized an Octopole Collision/Reaction Cell (CRC)‐equipped Quadrupole‐Inductively Coupled Plasma Mass Spectrometer for the rapid analysis of small volume samples ( 250 μL) in a variety of matrices containing HNO3 and/or HCl. Efficient elimination of polyatomic interferences was demonstrated by the use of the CRC in Reaction Mode (RM; H2 gas) and in Collision‐Reaction Mode (CRM; H2 and He gas), in addition to hot plasma (RF power 1500 W) and cool plasma (600 W) conditions. Results: It was found that cool plasma conditions with RM achieved the greatest signal sensitivity while maintaining low detection limits (i.e. 56 Fe in 0.44 M HNO3 has a sensitivity of 160, 000 counts per second (cps)‐per‐1 µg L –1 and a limit of detection (LoD) of 0.86 ng L –1 ). The average external precision was ≤ 10% for minor (≤10 µg L –1 ) elements measured in a 1:100 dilution of NIST 1643e and for iron in rainwater samples under all instrumental operating conditions. Conclusions: An improved method has been demonstrated for the rapid multi‐element analysis of trace metals that are challenged by polyatomic mass spectrometric interferences, with a focus on 56 Fe, 75 As, 78 Se and 111 Cd. This method can contribute to aqueous environmental geochemistry and chemical oceanography, as well as other fields such as forensic chemistry, agriculture, food chemistry, and pharmaceutical sciences. Copyright © 2015 John Wiley & Sons, Ltd.